The Impact of Digital Transformation on Organizational Performance and Operational Risks in Banking Sector - Rika Ayu Haryanti; Bimo Anugrah; Abi Gustama; Dwi Farid Rahmadani; Dewi Hanggraeni (Publikasi Indonesia, 2025)
This study examines the impact of digital transformation (DT) on organizational performance and operational risks in the banking sector. Internal factors analyzed include communication, comprehension of DT, operational technology readiness, process complexity, risk monitoring, and operational risk training, while external factors encompass regulatory compliance, digital experience, budget constraints, and cyber resilience. Using fuzzy-set qualitative comparative analysis (fsQCA) on survey data from 100 Indonesian banking professionals, the findings highlight the critical role of risk monitoring and operational technology readiness among internal factors, and cyber resilience and budget allocation among external factors. The interplay of these elements, such as combining risk monitoring with cyber resilience, is key to optimizing performance and mitigating risks. This study provides actionable insights for practitioners, policymakers, and scholars, emphasizing the alignment of internal capabilities with external demands. It highlights the importance of streamlined processes, cybersecurity frameworks, and supportive regulations for sustainable DT. While limited by sample size and subjective data, the research identifies opportunities for future studies, including cross-sectoral analyses and the use of objective performance metrics.